Mannan-decorated STING-activating vaccine carrier for spatial coordinative stimulating antigen-specific immune responses - Liping Liu; Jiayu Zhao; Zichao Huang; Yudi Xu; Hongyu Chen; Ruirui Qiao; Wantong Song; Zhaohui Tang; Thomas P. Davis; Xuesi Chen (Fundamental Research)
In recent years, the use of nanotechnologies to improve immunotherapy efficiency has attracted increasing interest in preventive and therapeutic cancer vaccine design. However, current nanocarriers are restricted by difficulties in the systematic spatial coordinative transport of antigens, which greatly hampers the immune response efficacy of nanovaccines. Herein, we designed a mannan-decorated stimulator of the interferon genes (STING)-activating vaccine carrier for spatial coordinative stimulation of antigen-specific immune responses and elicitation of robust antitumor immunity. Mannan-decoration as the shell could significantly enhance the lymph node draining ability of the nanovaccines, especially in CD8+ dendritic cells (DCs). Azole molecule end-capped polylactic acid-polyethylenimine (PLA-PEI-4BImi) with innate stimulating activity was applied as the inner core for coordinating antigen-presenting cell activation and antigen cross-presentation. In the in vivo therapy study, single usage of this nanovaccine could achieve a 93% tumor suppression rate in the B16-OVA tumor model, which is superior to the commercialized aluminum adjuvant. This study demonstrates that a rational design of vaccine carriers for solving spatial transmission issues could greatly improve cancer vaccine efficiencies.